Effectiveness of Vaginal Breech Birth Training Strategies: An Integrative Review of the Literature. Issue 1 (March 2018) - Walker, S.; Breslin, E.; Scamell, M.; Parker, P.
Abstract : ( Birth . 2017;44(2):101–109) Although most breech-presenting infants are born by cesarean section, the latest Cochrane Review on term breech delivery emphasized the importance of skills to facilitate vaginal breech birth and highlighted those skills as a research priority. The present integrative review aimed to identify and assess the effectiveness of breech birth training strategies according to the 4 levels of Kirkpatrick's levels of evaluation (reaction, learning, behavior, and results), and included both intended and unintended outcomes, as recommended by Yardley and Dornan. An additional objective of the present review was to gain insight into effective strategies of education about breech vaginal births.